2010
DOI: 10.1161/strokeaha.109.572693
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care and Outcomes in Patients With Diabetes Hospitalized With Ischemic Stroke

Abstract: Quality of care among patients with and without diabetes was similar except for rt-PA and cholesterol treatment. Diabetes was associated with worse stroke-related outcomes. Greater quality-improvement efforts to increase the use of rt-PA and other secondary prevention treatments in patients with diabetes are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
42
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 24 publications
11
42
1
Order By: Relevance
“…Our results are consistent with previous findings. 5,28 However, there has been a report in a Chinese population that showed that in-hospital mortality from ischemic stroke was not increased in patients with DM. 20 In our study, DM was significantly associated with death or dependency (mRSϭ3 to 6) in patients at 3 and 6 months after stroke onset, whereas the occurrence of coronary heart disease, pulmonary embolism, or peripheral artery disease showed comparable results between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with previous findings. 5,28 However, there has been a report in a Chinese population that showed that in-hospital mortality from ischemic stroke was not increased in patients with DM. 20 In our study, DM was significantly associated with death or dependency (mRSϭ3 to 6) in patients at 3 and 6 months after stroke onset, whereas the occurrence of coronary heart disease, pulmonary embolism, or peripheral artery disease showed comparable results between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Even though studies did not find overall reduced benefit of tPA in diabetic patients,12 decreased rates of tPA administrations are observed in diabetic patients 13. Guidelines recommend against tPA use in the 3‐ to 4.5‐hour window in patients with prior stroke plus diabetes based on insufficient evidence for its effectiveness, as patients with both prior stroke and diabetes were excluded from the European Cooperative Acute Stroke Study 3 trial 14.…”
Section: Introductionmentioning
confidence: 99%
“…This disease is associated with a polypathological condition, and its complications progressively affect quality of life and survival (Huang et al 2008;Eckert 2012). The many complications associated with diabetes include cardiovascular diseases, peripheral neuropathy, retinopathy, chronic renal failure, and impaired mental health (Blaum et al 2007;Maiorana et al 2002;Reeves et al 2010), which put diabetic patients in a polypathological condition (i.e., when diabetes coexists with two or more other diseases, such as hypertension, chronic renal failure, depression, and ischemic heart disease) (Rodríguez-Mañas et al 2014). In elderly populations, diabetes is also associated with reduced muscle strength, poor muscle quality, and accelerated loss of muscle mass (Morley 2008;Garg et al 2009;Leenders et al 2013;Park et al 2007;Volpato et al 2012;Morley et al 2014).…”
Section: Introductionmentioning
confidence: 99%